Effects of Acupotomy on Biomechanical Characteristics of Flexor and Extensor Muscle Groups and Cartilage Degeneration in Rabbits with Knee Osteoarthritis - GAO Hainan; ZHANG Mengyi; LIU Xi; ZHONG Peirong; TANG Yanjuan; SHAO Xinxin; TAN Zili; ZHU Xiangyu (康复学报)
ObjectiveTo study the effects of acupotomy on the muscle function of the flexor and extensor muscle groups, and cartilage degeneration in rabbits with knee osteoarthritis, and comprehensively explore the biomechanical mechanism of acupotomy in the treatment of KOA.MethodsSixty male New Zealand rabbits were divided into a blank group, a model group, an acupotomy group, and an electroacupuncture group using the random number table method, with 15 rabbits in each group. After the modeling was completed, samples with abnormal body weight, those that had died, and those with failed modeling were excluded. Finally, 48 samples were included, with 12 samples in each group. The modified Videman method was used to establish the model for eight weeks, and the acupotomy group and the electroacupuncture group were intervened for three weeks. The Lequesne MG score was used to detect the pathological changes of KOA and explore the effect of acupotomy on the behavior of KOA rabbits. One week after the intervention ended, the Myoton Pro digital muscle function assessment system was used to detect the muscle physical characteristic values of the flexor and extensor muscle groups of rabbits in each group, including oscillation frequency, dynamic stiffness, logarithmic decrement, mechanical stress relaxation time, and Deborah number (creep). The rabbits in each group were anesthetized to death, the knee joint surfaces were observed and scored using the Peng Taiping method and the articular cartilage was isolated and stained with safranin O-fast green respectively. The morphological distribution of cartilage tissue was observed to explore the effect of acupotomy on cartilage degeneration in KOA rabbits.Results① Severity of knee arthritis：after the intervention, compared with the normal group, the Lequesne MG score of the model group was increased (P<0.05). Compared with the model group, the Lequesne MG score of the acupotomy group was decreased (P<0.05), and that of the electroacupuncture group was also decreased (P<0.05). ② Physical characteristics of muscles：compared with the normal group, the Oscillation Frequency, Dynamic Stiffness, Mechanical Stress Relaxation Time and Creep of the flexor and extensor muscle groups in the model group, electroacupuncture group and acupotomy group both before and after treatment increased (P<0.05), and the Logarithmic Decrement decreased (P<0.05), with significant differences. Compared with the model group, the Oscillation Frequency, Dynamic Stiffness, Mechanical Stress Relaxation Time and Creep of the flexor and extensor muscle groups in the acupotomy group and the electroacupuncture group, after treatment, were all decreased (P<0.05), while the Logarithmic Decrement was increased (P<0.05), showing significant differences. Compared with the electroacupuncture group, the Oscillation Frequency of both the flexor and extensor muscle groups in the acupotomy group , after treatment, decreased (P<0.05). And, the Dynamic Stiffness of the flexor muscle group decreased (P<0.05), while the Logarithmic Decrement increased (P<0.05). These differences were statistically significant. Compared with the pre-treatment values, the Oscillation Frequency, Dynamic Stiffness, Mechanical Stress Relaxation Time and Creep of the flexor and extensor muscle groups in the acupotomy group and the electroacupuncture group, after treatment, were all decreased (P<0.05), while the Logarithmic Decrement was increased (P<0.05), showing significant differences. ③ Pathological and morphological characteristics：macroscopic observation of the articular surfaces of rabbits in each group：Compared with the normal group, the joints in the model group were swollen, with cartilage defects on the articular surfaces, abundant osteophytes, and turbid synovial fluid. The appearance of the joints in the acupotomy group was basically normal, with occasional superficial wear on the cartilage surface. The articular surfaces in the electroacupuncture group were locally rough, with a small number of osteophytes, a large amount of synovial fluid, and a slightly turbid appearance. Scoring of the articular surfaces of rabbits in each group using the Taiping Peng's method：Compared with the normal group, the model group was mainly at grade III, while the acupotomy group and the electroacupuncture group were mainly at grade II. For safranin O-fast green staining, compared with the blank group, the cartilage matrix in the model group was unevenly distributed in patches, the chondrocytes were clustered, and the tidemark was blurred. Compared with the model group, the cartilage matrix staining in the acupotomy group and the electroacupuncture group was slightly more uniform, the number of chondrocytes increased, some of the cartilage layers were clear, the tidemark was partially restored, and the subchondral bone became shallower.ConclusionAcupotomy can effectively improve the physical properties of skeletal muscles, delay the degradation of knee joint cartilage in KOA rabbits in the flexor and extensor muscle groups. This provides a theoretical basis for the clinical application of a Acupotomy therapy in the treatment of KOA.